The Effect of Juice Clarity and Several Conditions Promoting Yeast Growth on Fermentation Rate, the Production of Aroma Components and Wine Quality - Houtman, A. C.; Du Plessis, C. S. (South African Journal of Enology and Viticulture, 2017)
In cellar practice grape juice is preferably made as clear as possible, and fermentations take place under strictly anaerobic conditions. In the laboratory, however, the fermentation rate of EK-filtered and de-aerated juices was always so much slower than that of juices obtained by normal cellar routine that no dry wines could be prepared unless fermentation stimulating methods were applied. Apparently in most cellar fermentations sufficient amounts of oxygen and/or of yeast growth promoting steroids from the grapes are present to complete fermentation, but the exact amounts present are unknown. In practice problems with lagging fermentation could occur in cases where clarifying and de-aeration of juice were performed too rigorously. Grape juice was clarified by diverse methods, and white wines were prepared from the juices under various conditions in order to study the effect of de·aeration, addition of settled juice with residual turbidity, micro-aeration and application of ergosterol suspensions on fermentation rate. EK-filtered juices were used to experiment with methods for reactivating lagging fermentation and also for investigating the effect of fermentation conditions on the production of wine volatiles. With the aid of the above-mentioned fermentation stimulating means the fermentation of EK-filtered juices could be completed within an acceptable period of time. Steps to reactivate lagging fermentations should be taken as early as possible, although additions of settled juice were often successful, even when applied at a late stage during fermentation. Filtered juice from different cultivars and origins behaved in a markedly similar way with regard to fermentation and the production of volatile components. Filtration of juice caused partial loss of the cultivar character of the wine but wines from filtered juice with additions of ergosterol were nevertheless allotted the highest scores during organoleptic evaluation. The production of higher alcohols depends on the degree of juice turbidity and fermentation temperature. In clear filtered juice, however, the production of higher alcohols was independent of fermentation temperature. The formation of acetates of higher alcohols is greatly enhanced, by adding ergosterol to the filtered juice.